The Contemporary Role of Masked Continuous Glucose Monitoring in a Real-Time World. (May 2016) - Blumer, Ian
Real-time continuous glucose monitoring (RT-CGM) has, in the span of just a few years, established an essential role in the contemporary management of type 1 diabetes. Nonetheless, masked CGM retains an important place in the management of diabetes including assisting with hypoglycemia detection and avoidance, optimizing glycemic control, and acting as a teaching tool for people living with diabetes.